Computer-based support for clinical guidelines and protocols: Proceedings of the symposium on computerized guidelines and protocols (CGP 2004) - Kaiser, Katharina (IOS, 2013)
In recent years, guidelines and protocols have gained support as the vehicles for promoting best practices in clinical medicine. They offer the possibilities of reducing unwarranted practice variations, of containing cost while maintaining quality of care, and of defining standards of care for quality assurance purposes. These promises have led to an explosion of guideline publications. Yet studies have shown that dissemination and effective use of guidelines in clinical care remains a major bottleneck. A number of researchers have developed different technologies for delivering computerized guidelines in clinical care. These technologies range from alerts and reminders to knowledge-based systems, information-retrieval systems, and others. The tasks to which guidelines have been applied include classic clinical decision support, workflow management, quality assurance, and resource-requirement estimates. The research has spanned several communities (information retrieval, artificial intelligence, medical informatics, software engineering, clinical medicine), but unfortunately, there has been little cross-fertilization between the communities working in this area. This publication brings together researchers from different communities to examine cutting-edge approaches to guideline modeling and application development and to consider how different communities can leverage each other's strengths.